2004
DOI: 10.22146/ijcn.17397
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi obesitas dan hubungan konsumsi fast food dengan kejadian obesitas pada remaja SLTP kota dan desa di Daerah Istimewa Yogyakarta

Abstract: Background: The improvement in socioeconomic status has led to sedentary life style and more fast food consumption. Whether fast food consumption contributes to obesity in Indonesian adolescents remains unclear.Objective: The study was conducted to estimate the prevalence of obesity and to assess the association between fast food consumption and obesity in junior high school students.Methods: A cross-sectional survey was conducted in 2003 to estimate the prevalence of obesity in adolescent students of Yogyakar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
1
4
0
12
Order By: Relevance
“…Based on the results of the study found that more than four-five samples (83.0%) at least consume fast food one to three times a week. This figure looks low, but according to research by Mahdiah et al (2004) in adolescents in Yogyakarta, Indonesia shows that consuming fast food more than four times per month tends to cause obesity. Other results show that more than half (60.4%) of samples consume fast food in restaurants that provide fast food and more than two-fifths (41.7%) of them eating with friends.…”
Section: Discussionmentioning
confidence: 96%
“…Based on the results of the study found that more than four-five samples (83.0%) at least consume fast food one to three times a week. This figure looks low, but according to research by Mahdiah et al (2004) in adolescents in Yogyakarta, Indonesia shows that consuming fast food more than four times per month tends to cause obesity. Other results show that more than half (60.4%) of samples consume fast food in restaurants that provide fast food and more than two-fifths (41.7%) of them eating with friends.…”
Section: Discussionmentioning
confidence: 96%
“…Di Indonesia dan beberapa negara berkembang, prevalensi obesitas lebih banyak ditemukan pada remaja yang tinggal di wilayah perkotaan dibandingkan di wilayah pedesaan. 3,10 Hal ini menunjukan peran gaya hidup dan modernisasi sebagai faktor penting terhadap munculnya fenomena kegemukan. Beberapa komponen gaya hidup yang paling menonjol dan berkontribusi terhadap kejadian obesitas pada anak dan remaja adalah tingginya asupan energi harian dan rendahnya aktivitas fisik.…”
Section: Abstract Obesity Prevention; Adolescents; School; Lifestyleunclassified
“…38 Perilaku konsumsi fast food diketahui menjadi faktor risiko terhadap obesitas pada remaja di beberapa wilayah di Indonesia seperti Yogyakarta (7,9% di daerah perkotaan) dan Minahasa (26,33%). 39,40 Kondisi berat badan lebih dan obese pada komunitas etnik Halmahera Utara dapat dipengaruhi perilaku konsumsi makanan yang berlebihan. Pola hidup seperti diet dan olahraga berpengaruh terhadap nilai IMT.…”
Section: Pembahasanunclassified